Critical factors influencing cost estimators' judgements on cost contingencies in highway construction projects: An empirical study in the UK. - Lilin Zhao; Jinpeng Wang; Shang Zhang (PLoS ONE)
Unforeseen additional costs are major sources of cost overruns for the UK's highway projects. General contractors normally allocate cost contingencies in their tender prices to cover these costs, primarily based on the judgements of their cost estimators. However, cost contingencies allocated to the same risk by different cost estimators can vary significantly. Although objective factors influencing the estimation of cost contingencies have been extensively investigated, subjective factors remain underexplored. Therefore, this paper aims to address this gap by investigating the subjective factors influencing cost estimators' judgements through a qualitative study. Twelve semi-structured interviews were conducted with experienced cost estimators working for general contractors in the UK's construction industry. A follow-up focus group study was also conducted with seven experienced cost estimators in the UK's construction industry to validate the interview results. The findings reveal that there are thirteen influencing factors affecting cost estimators' judgements on cost contingencies in highway construction projects. Seven of them, namely cost estimators' ability to effectively communicate with stakeholders, self-reflection on previous practice, open-mindedness to project uniqueness, previous project experiences, risk attitude, assumption of the controllability of risks, and perceived quality of tender documents were identified as critical ones. They were grouped into two categories, including expertise-related factors and personal factors. The findings contribute to the lack of research on the subjective factors influencing cost estimators' judgement-making process in highway construction projects in developed countries. The results also provide new practical insights for general contractors to develop more focused strategies and training programs to enhance the reliability of cost estimators' judgements on cost contingencies, which can effectively reduce the probability of cost overruns.